Challenging conservation agriculture on marginal slopes in Sehoul, Morocco. Issue 3 (June 2015) - Schwilch, G.; Laouina, A.; Chaker, M.; Machouri, N.; Sfa, M.; Stroosnijder, L.
Abstract In Sehoul, Morocco, the use of marginal land for agriculture became a necessity for the local population due to increased poverty and the occupation of the best land by new owners. Desertification poses an additional threat to agricultural production on marginal slopes, which are often stony and degraded. In a participatory process embedded in the EU DESIRE research project, potential sustainable land management measures were selected to address land degradation and desertification. Promising experiences with no-tillage practices elsewhere in Morocco had motivated the Moroccan government to promote conservation agriculture throughout the country. This combination of crop rotation, minimal soil disturbance and soil cover maintenance, however, had not yet been tested on sloping degraded land. Field trials of grazing enclosure combined with no or minimum tillage were conducted on the plots of two farmers, and trial results were analyzed based on stakeholders' criteria. Results suggest that increased soil cover with barley residues improved rainwater use efficiency and yields only slightly, although soil water was generally enhanced. Soil moisture measurements revealed that no-tillage was favorable mainly at soil depths of 5 cm and in connection with low-rainfall events (<20 mm); under these circumstances, moisture content was generally higher under no-tillage than under conventional tillage. Moreover, stakeholder discussion confirmed that farmers in Sehoul remain primarily interested in animal husbandry and are reluctant to change the current grazing system. Implementation of conservation agriculture is thus challenged both by the degraded, sloping and stony nature of the land, and by the socio-economic circumstances in Sehoul.